(3GdQbGHI GdMchejI Ydi JCSjS GdTQcGJ (B:s (3OQGSI ebGQfI (B/s - (3YHjOGJ, eDjO eMj GdOjfs ((3YeGf(B: s (3GdMGeO(B, s, 2008)
(3GdJWhQ GdJGQjNj ddQbGHI GdSGHbI aj HYV GdJTQjYGJ h eaghe GdQbGHI GdSGHbI Ydi GdTQcGJ h JaQjRgG YeG jTJHg eYgG h CgOGagGh ehba GdJTQjYGJ GdSGHbI efgG , GdLgGJ GdJj JeGQS GdQbGHI GdSGHbI Ydi GdJCSjS h cPdc eSJdReGJ GdJCSjS h GdQbGHI Ydjg h CNjQG eVehf GdQbGHI GdSGHbI (B.s
(3GdeQGLY U(B.369 ((3GbJfGAGJ (B2014 3(3f(B)s
Keywords: (3GdTQcGJs; (3bGfhf GdTQcGJs